Driving Educational in Management Excellence: The Interconnected Roles of Cautious Thinking and Cooperation Capability for Successfully in Cognitive Presence - Sisrayanti; Asmar Yulastri; M Giatman; Fadhilah (The Indonesian Journal of Computer Science, 2023)
In the realm of education, the dynamics of learning have always been a subject of keen interest and in-depth investigation. This research explores the intricate relationship between cautious thinking, cooperation capability, and cognitive presence within the educational context. The results of data analysis indicate that these three variables have a strong and significant relationship. Notably, cautious thinking plays a pivotal role in enhancing students' critical thinking abilities, while cooperation capability exerts a positive influence on their cognitive presence. These findings provide a solid foundation for understanding the pivotal roles of cautious thinking and cooperation capability in elevating the quality of students' learning experiences. Furthermore, the implications of this research resonate profoundly in the field of management, offering the promise of enhancing educational practices and human resource development. With a hopeful outlook, the researchers anticipate that the outcomes of this study will serve as a stepping stone for further research and will contribute substantially to the ongoing enhancement of educational standards and management practices in the future.